Pengembangan LKPD PAK Berbasis Android Dengan Pendekatan Contextual Teaching and Learning (CTL) Pada Siswa Kelas V - Simanjuntak, Pahala Mulatua; Ismanto, Bambang; Wasitohadi, Wasitohadi (Universitas Kristen Satya Wacana, 2025)
This research is motivated by the lack of learning media as a means of learning activities. While technology has been growing and the limitations of learning media in schools are not a barrier to progress but become the basis for making a breakthrough or educational innovation. This study aims to develop and test the validity of the LKPD PAK product for fifth grade students. This type of research is Research and Development (R&D) with the ADDIE model. However, it is only limited to the development stage (validity test). The development of this LKPD includes designing interesting materials, describing student activities and providing evaluation questions. The subject of the validity test is 1 lecturer and 2 Christian teachers. The three validators validate the LKPD that has been made, which consists of educational technology experts and material experts. The three validators will assess in terms of the aspects that become indicators. The data collection techniques used are observation, interviews and questionnaires. The specifications on this product are in the form of a LINK which has learning features according to the development of the material being carried out. The product of this research has fulfilled the validity aspect so that it can be used as an alternative teaching material for teachers to use in the learning process. The development of Android-based LKPD with a contextual teaching and learning approach on the meaning of sin and the impact of sin can be carried out on other learning materials or can even be applied to other subjects.